Adverbs of Comment and Disagreement - Liu, Mingya (Proceedings of the Amsterdam Colloquium, 2009)
Adverbs of comment (AOCs) such as sadly, fortunately raise a question of subjective meaning, much like predicates of personal taste (fun, tasty), namely, to whom the speaker attributes the emotion or evaluation, when there is no overt for-PP. I extend Lasersohn’s (2005) judge parameter to the analysis of AOCs and propose that disagreement on one and the same proposition only arises when the hearer correctly resolves the argument of judge despite its absence in overt syntax, i.e. sad(p,c) vs. ¬sad(p,c). Otherwise, only mis- or incomprehension occurs where the speaker and the hearer actually express two different propositions on the same issue, i.e. sad(p,c) vs. ¬sad(p,b).